2016
DOI: 10.1111/epi.13321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selective serotonin and norepinephrine reuptake inhibitors on depressive‐ and impulsive‐like behaviors and on monoamine transmission in experimental temporal lobe epilepsy

Abstract: Summary Objective Examine therapeutic potential of a selective serotonin reuptake inhibitor (SSRI) and a norepinephrine reuptake inhibitor (NERI) in an animal model of comorbidity between epilepsy, depression-like, and impulsive-like impairments. Methods Epilepsy was induced in male Wistar rats by LiCl and pilocarpine. An SSRI fluoxetine (FLX), and a NERI reboxetine (RBX) were administered either alone or as a combination over one week. Depressive-like and impulsive-like behaviors were examined using forced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 37 publications
2
33
0
5
Order By: Relevance
“…Currently, more and more experimental and clinical research demonstrated the bidirectional relation between epilepsy and associated comorbidities [61][62][63]. Patients with epilepsy, especially with disabling epilepsy, clinically demonstrate not only recurrent seizures, cognition deficits and psychiatric symptoms such as depression and psychosis.…”
Section: Overexpression Of Adk and Comorbidities Associated Epilepsymentioning
confidence: 99%
“…Currently, more and more experimental and clinical research demonstrated the bidirectional relation between epilepsy and associated comorbidities [61][62][63]. Patients with epilepsy, especially with disabling epilepsy, clinically demonstrate not only recurrent seizures, cognition deficits and psychiatric symptoms such as depression and psychosis.…”
Section: Overexpression Of Adk and Comorbidities Associated Epilepsymentioning
confidence: 99%
“…Both behaviors are present in normal and depressed animals, but in models of depression, the animals spend longer time immobile, which is interpreted as a hopelessness/despair state. Cumulative time spent immobile was calculated [29, 30]. …”
Section: Methodsmentioning
confidence: 99%
“…In order to alleviate the severity of SE and to decrease the frequency of subsequent spontaneous seizures, rats received i.p. injections of diazepam (10 mg/kg) and phenytoin (50 mg/kg) one and four hours after the SE onset (Kumar et al, 2016; Mazarati et al, 2008; Pineda et al, 2014; Pineda et al, 2012). In control animals, saline was injected instead of pilocarpine.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…FST was used to examine depressive- and impulsive-like behaviors as described by our group (Kumar et al, 2016; Mazarati et al, 2008; Pineda et al, 2014). The first FST (FST 1 ) was performed 4 weeks after SE; the second (FST 2 ) was conducted during the administration of GalR ligands; some animals underwent the third test (FST 3 ) after the drug washout (Fig.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation